PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPA TENTANG EKOSISTEM - Fembriani .; Ribka Polin; Adam B Benu (Journal of Character and ELementary Education, 2022)
The purpose of this research is to determine effect problem based learning (PBL) learning model on student learning outcomes on ecosystem material in grade V SD Negeri Nunbaun Sabu. This descriptive quantitative research uses quasi experimental type experimental method type non equivalent control group design. Population in this study was grade V students of Nunbaun Sabu State Elementary School which 53 students. The research sample was a VA class of 26 students as an experiment class and a VB class of 27 students as a control class. The treatment applied to the experiment class is a model of problem based learning while in the control class is a lecture. There are 5 steps in applying problem based learning model namely 1) student orientation on the problem,2) organizing students to learn 3) guiding individual/group experience, 4) developing and presenting the work, 5) analyzing and evaluating the problem solving process. Results showed that there is an influence from the use of problem based learning models on students' learning outcomes. The average score difference in the experiment class was 34.07 higher than the average difference between the control classes and the mean= 16.07 difference was significant with the price of sig. (2-tailed) 0.000 (or p> 0.05). The amount of treatment effect on the yield of bealajar of 0.77 ata is equivalent to 59% that is included in the category of large effects.